Cost of regulation and impact of EU membership on policy enforcement - Phedon A. Nicolaides (Intereconomics, 2013)
Recent public debate on the costs and benefits of EU membership has focused more on the costs and less on the benefits. This paper explores the benefits from improved regulatory or policy implementation and enforcement. If actual regulatory enforcement differs from the socially optimal level, membership of a regional bloc that strengthens accountability mechanisms can improve the quality of implemented regulation. However, if the regional bloc tends to over-regulate, the overall increase in the regulatory burden, together with strengthened accountability, will move a country farther away from its socially optimal state. Membership of the EU is beneficial for countries with weak enforcement institutions, but it may worsen the welfare of countries with strong regulatory institutions. Infringement statistics indicate that no member state of the EU has a perfect record in implementation and enforcement.
Keywords: 330